O papel do idoso na família contemporânea - Ohara, Elisabete Calabuig Chapina (2012)
The family and the elderly are an essential part of nursing care, being necessary for the professional to open themselves to the family to understand experiences and worldviews. This interdisciplinary study was intended to reflect on the major changes that involve the aging process and the diversity that characterizes it, going to their meanings and social changes that reflect in the family as an institution. The study objectives were: reflect on the changes the Brazilian family has gone through and the impact of these changes on the role of the elderly in the contemporary family; identify the cultural, social and subjective aspects of the elderly and their families; meet the family dynamics and their meanings for the elderly; understand how the elderly s family structures itself, its development and functioning. Focusing on this, we opted for conducting qualitative research with small groups (elderly and their relatives); the fieldwork - participatory observation of those small groups and long interviews anchored, in dialogue with the specialized literature, the proposed interpretations. The chosen families should meet any of the following requirements for the study: the elderly s family should be experiencing changes in social aspect (retirement; unemployment, volunteering, widowhood, financial hardship); the elderly in the family as the primary provider (household income is centered on the elderly s pension); the elderly as caregiver for grandchildren; the family as caregiver for the elderly; the elderly experiencing motivating experiences. Everyone involved in this research (elderly and family) accepted to participate. The questionnaire for the interview was composed of open-ended questions (this was seen as a provocation to the dialogue and within the limits, reminders, so that it was possible to have material for comparison). The technique used for analysis made it possible to build a multiplicity of complex structures, overlapping or tied to each other, which may be different, irregular and that initially should be learnt and then interpreted and presented. (GEERTZ, 1989) Content analysis was also performed with the aid of a software (International QSR Nvivo 9 project-Environmental Change Down East), developed by researchers working with qualitative research in the area of social sciences. The family roles in today's world have changed due to the complexity of situations created by economic and sociocultural factors directly affecting the family dynamics. The basic functions of the elderly in the family are varied, above all others as the educator, with specific functions such as ensuring religious, cultural, economic and social aspects, while the role of the family (family group) is to take care of the children, the elderly and the sick. Knowledge about the role of elderly people in the contemporary family allowed for paths to professional practice. We also believe that the studied aspects can contribute to a new theoretical and interdisciplinary perspective of the object and, especially, contribute to the training of health, social sciences and education professionals. We believe that by giving voice to seniors, we provoke their own change and consequently help in breaking down the prejudices and myths about them, enabling the opening of roads to the rescue of their active citizenship and the achievement or maintenance of their place in the family and in society. It is concluded that the study is a tool for professionals who seek a better understanding of the variables that interfere with aging, family and the community